Hubungan Fungsi Kognitif Lansia dengan Tingkat Kemandirian Lansia di Posyandu Lansia Kelurahan Balearjosari Malang - Heni Atiqah; Sih Ageng Lumadi (Jurnal Ilmiah Kesehatan Rustida, 2020)
Based on research in Indonesia the decline in cognitive function in the elderly was 121 million people, 5.8% male and 9.5% women. So 50% of elderly people show cognitive function. This certainly will affect the cognitive function of the elderly which has implications for independence in carrying out activities. The purpose of this study was to determine the relationship of cognitive function of the elderly with the level of independence of the elderly at the Posyandu Kelurahan Balearjosari Malang. The design of this study uses correlational with a cross sectional approach. The population in this study was elderly with a sample of 63 elderly using total sampling. Data collection used interview guidelines with Mini Mental Exame and Index Katz. Analysis of spearman correlation test data using the SPSS program. The results of the analysis are obtained (r count) of 0.398 with p= 0.001 where the p-value < 0.05 means Ha is accepted, so it can be concluded that there is a relationship between the cognitive function of the elderly with the level of independence of the elderly at the Posyandu Kelurahan Balearjosari Malang. Thus if the cognitive function in the elderly decreases. The level of independence will decrease. This research is expected to be us a reference in condicting furtherbresearch. Including research that can be associated with factors that influence cognitive function of the elderly and the level of independence of the elderly and the importance of family support in providingmotivation to the elderly.